Odgovornost za neupravičeno odstranitev spletnih vsebin - Damjan, Matija (Pravni letopis, 2022)
A web hosting provider guarantees the users of its services that the content they upload to the provider’s server will remain accessible to other internet users. An outage in online availability of the users’ content can cause damage to the provider’s customers. However, hosting providers are obliged by law to remove their users‘ content if they receive a notification from a third party that the content is unlawful. The article examines the liability for damage caused by the temporary inaccessibility of the removed online content if it subsequently turns out that the takedown request was unfounded. Discussed are the conditions under which the person who submitted an unfounded takedown request can be held liable for damages as well as the conditions for the liability of the web hosting provider who unjustifiably removed the content or disabled access to it. The article also outlines how the issues in question will be affected by the revised regulation of the notice-and-takedown system brought about by the Digital Services Act.
Keywords: Akt o digitalnih storitvah; dostopnost; internet; nezakonite spletne vsebine; odgovornost; odškodninska odgovornost; spletno gostovanje